Prospective evaluation of heparin-induced thrombocytopenia expert probability and 4T scores in Chinese patients with suspected heparin-induced thrombocytopenia - Li, Sen (Chin Med J (Engl), 2019)
BACKGROUND: Diagnosis of heparin-induced thrombocytopenia (HIT) is challenging. This study aimed to compare the diagnostic performance of HIT expert probability (HEP) and 4T scores, and to evaluate the inter-observer reliability for the 4T score in a clinical setting. METHODS: This prospective study included HIT-suspected patients between 2016 and 2018. Three hematologists assessed the HEP and 4T scores. Correlations between scores and anti-platelet factor 4 (anti-PF4)/heparin antibodies were evaluated. Receiver operating characteristic curves and area under the curve (AUC) were used to assess the predictive accuracy of these two scoring models. The intraclass correlation coefficient (ICC) was used to assess the inter-observer agreement of 4T scores between residents and hematologists. RESULTS: Of the 89 subjects included, 22 (24.7%) were positive for anti-PF4/heparin antibody. The correlations between antibody titer and either HEP or 4T scores were similar (r = 0.392, P < 0.01 for the HEP score; r = 0.444, P < 0.01 for the 4T score). No significant difference in the diagnostic performance was displayed between these two scores (AUC for the HEP score: 0.778 vs. AUC for the 4T score: 0.741, P = 0.357). Only 72 4T scores were collected from the residents, with a surprisingly low percentage of observers (43.1%) presenting the four individual item scores which made up their 4T score. The AUC of 4T score assessed by residents and hematologists was 0.657 (95% confidence interval [CI]: 536–0.765) and 0.780 (95% CI: 0.667–0.869, P < 0.05), respectively. The ICC of 4T score between residents and hematologists was 0.49 (95% CI: 0.29–0.65, P < 0.01), demonstrating a fair inter-observer agreement. CONCLUSIONS: The HEP score does not display a better performance for predicting HIT than the 4T score. With the unsatisfactory completion rate, the inter-observer agreement of 4T score in a tertiary hospital is fair, underscoring the necessity for continuing education for physicians.